Peningkatan Kapasitas Kelompok Home Industri Pandebassi di Desa Pamboborang dalam Penggunaan Digital Marketplace - Riady Ibnu Khaldun; Rezky Ramadhan Antuli; Muhammad Sajidin; Nursafila, Nursafila; Mus Muliadi (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
In the current digital era, the ability to leverage technology and online platforms has become a key factor for success across various industries, including home industries. One example is the Pandebassi home industry group in Pamboborang Village, which has enhanced its capacity to use digital marketplaces to promote its products. Pandebassi consists of a group of local artisans in Pamboborang Village. Previously, they faced challenges in marketing their products due to limited market access and a lack of knowledge about how to utilize online platforms. To overcome these challenges, the group decided to improve its capacity in using digital marketplaces. The training helped them understand the basics of online marketing, sales strategies, and product optimization techniques to increase online visibility. With increased income from online sales, the group was able to improve product quality, expand market reach, and empower more members within the group. Additionally, the success of the Pandebassi group in utilizing digital marketplaces is expected to have a positive impact on the local economy in Pamboborang Village. With the growth of their online business activities, more job opportunities are created for the local community, contributing to better economic growth. In conclusion, the capacity enhancement of the Pandebassi home industry group in Pamboborang Village in using digital marketplaces is expected to have a significant impact on local economic development and the welfare of group members. This demonstrates the importance of leveraging technology to develop home industries and expand market access for small and medium-sized enterprises.